2013
DOI: 10.1007/s12149-013-0753-1
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between SPECT V/Q scan and CT angiography in patients with high clinical suspicion of PE

Abstract: In the presence of an indeterminate CTA in patients with high clinical suspicion of PE, SPECT V/Q often provides a diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
0
9
0
3
Order By: Relevance
“…Among 100 high-risk patients who required both V/Q SPECT and CT angiography due to an initial indeterminate or negative imaging test despite a high pre-test probability, the agreement between these tests was evaluated [23]. Pulmonary embolism was diagnosed by clinical findings as well as the results of V/Q SPECT and CT angiography.…”
Section: Non-diagnosticmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 100 high-risk patients who required both V/Q SPECT and CT angiography due to an initial indeterminate or negative imaging test despite a high pre-test probability, the agreement between these tests was evaluated [23]. Pulmonary embolism was diagnosed by clinical findings as well as the results of V/Q SPECT and CT angiography.…”
Section: Non-diagnosticmentioning
confidence: 99%
“…Computed tomographic angiography was diagnostic in 10 out of 12 (83 %) patients in whom V/Q SPECT was indeterminate. Ventilation/perfusion SPECT often provides a diagnosis in the presence of an indeterminate CT angiogram in patients with high clinical suspicion of PE, and CT angiography often provides a diagnosis when SPECT is indeterminate [23]. These data suggest that in difficult cases the two modalities can be complementary.…”
Section: Non-diagnosticmentioning
confidence: 99%
See 1 more Smart Citation
“…Bajc et al and a prospective study by Gutte et al showed that V/P SPECT has higher sensitivity and specificity and less non-diagnostic findings than MDCT [10,14]. A recent study by Mahdavi et al showed that in the presence of an indeterminate CT angiography (CTA) in patients with high clinical suspicion of PE, V/P SPECT often provides a diagnosis [15].…”
Section: Comparison With Mdctmentioning
confidence: 99%
“…MAA in labeling with 99m Tc, 99m Tc-MAA, has been introduced for different use such as perfusion lung imaging to assess the presence of pulmonary emboli, radionuclide venography to identify lower extremity venous thrombosis and assessment of peritoneovenous shunt patency [7,8]. Due to the special characteristics of 68 Ga and MAA, it seems 68 Ga-MAA complex can be a potential PET imaging agent [9].…”
Section: Introductionmentioning
confidence: 99%